Parental bereavement: Looking beyond grief. Issue 5 (28th May 2017) - Dias, Nancy; Docherty, Sharron; Brandon, Debra
ABSTRACT: Bereaved parents have higher morbidity and mortality rates when compared to nonbereaved parents. Although parental grief is well studied, the complexities of challenges bereaved parents face are not understood. This study describes parental bereavement challenges during the first 6 months following the death of their child. The complex parental bereavement challenges are characterized by the absence of the child, their emotional response, and the changed relationships with family and friends. The adaptive leadership framework is a useful framework to identify and classify challenges. Future research can use this framework to provide a structure that test interventions to address the challenges.